THE CORRELATION BETWEEN KNOWLEDGE AND FOOD SELECTION PRACTICES AND HAZARDOUS SUBSTANCES AMONG JUNIOR HIGH SCHOOL STUDENTS - Cindy Zerlina Artanti; Linda Dewanti; Ira Dharmawati (The Indonesian Journal of Public Health, 2022)
Introduction: There are many cases of food poisoning in Surabaya. Furthermore, there are also many food vendors around the school and canteen using hazardous substances which can cause food poisoning. The aim of this study was to analyze the association between knowledge and food selection practices among students at one of junior high schools in East Surabaya towards hazardous substances. Methods: The methods of this is an analytic-observational study with a cross-sectional design which used primary data from the student who fills out the questionnaire. The study sample includes 119 students at junior high school 19 Surabaya, Indonesia, range of age 12-14 years old. The dependent variable in this study food selection practices, the independent variable was level of knowledge of hazardous substances. The study used 4 questionnaires to collect the data. Data collection was carried out in December 2019, this study used simple random sampling and the data analyzed by Chi-Square Test. Result: The results of this research showed that 52.9% of students have knowledge category ‘moderate’ and 47% of students ‘food selection practices’ category ‘correct’. This research showed that there was no significant correlation between knowledge and food selection practices. Conclusion: The conclusion of this study there was no significant correlation between  knowledge and food selection practices towards on hazardous substances, it must another factor that could be affected the decision of adolescents. Keywords: food poisoning, food selection, knowledge, food vendor, hazardous substances, schoolchildren